2003
DOI: 10.1667/0033-7587(2003)159[0003:csflee]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections for Low-Energy (1–100 eV) Electron Elastic and Inelastic Scattering in Amorphous Ice

Abstract: We report the integral cross sections per scatterer (i.e. elastic collision, phonon excitations, vibrational excitations, electronic excitations and ionization) for 1-100 eV electron scattering in an amorphous film of ice condensed at a temperature of 14 K. The integral cross sections are determined relative to the total from a two-stream multiple-scattering analysis of the electron energy distribution backscattered from the film. Their energy dependence is obtained from both the analysis of the elastic electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
311
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(339 citation statements)
references
References 81 publications
23
311
4
1
Order By: Relevance
“…47,48,55,56 It has to be pointed out, that photoelectron spectroscopy is in general a surface sensitive technique due to the limited escape depth of photoelectrons. In water, the escape depth of photoelectrons with kinetic energies of about 20-30 eV -the kinetic energies relevant to our experiment -is about a few nanometers [57][58][59][60] and thus about several layers of water molecules from the surface only. 61 Therefore, the experiment senses the interface and the condensed phase at t = 0 and the evolution of the hot superheated phase at t 4 0.…”
Section: Introductionmentioning
confidence: 82%
“…47,48,55,56 It has to be pointed out, that photoelectron spectroscopy is in general a surface sensitive technique due to the limited escape depth of photoelectrons. In water, the escape depth of photoelectrons with kinetic energies of about 20-30 eV -the kinetic energies relevant to our experiment -is about a few nanometers [57][58][59][60] and thus about several layers of water molecules from the surface only. 61 Therefore, the experiment senses the interface and the condensed phase at t = 0 and the evolution of the hot superheated phase at t 4 0.…”
Section: Introductionmentioning
confidence: 82%
“…For this purpose, nine more phonon and vibrational excitation states and the formation of two transient anion states were considered in addition to each of the five ionisation and electronic excitation levels. The total cross sections for these additional physical processes were taken directly from Michaud et al (2003). The energy loss for each level was determined by random sampling from a Lorentzian probability distribution function (PDF).…”
Section: Interaction Cross Section Data In Ptra and Geant4-dnamentioning
confidence: 99%
“…The energy loss for each level was determined by random sampling from a Lorentzian probability distribution function (PDF). The maximum of the PDF was at the mean excitation energy of each excitation state, provided by Michaud et al (2003), and a full width half maximum as suggested by Dingfelder et al (2008). Following the example of Dingfelder et al (2008), the scattering angle after phonon and vibrational excitation were assumed to be the same as for elastic scattering, while dissociative attachment anion states were assumed to not lead to a change in direction.…”
Section: Interaction Cross Section Data In Ptra and Geant4-dnamentioning
confidence: 99%
See 2 more Smart Citations